Increasing Rate of Fatal Streptococcus pyogenes Bacteriemia-A Challenge for Prompt Diagnosis and Appropriate Therapy in Real Praxis - Adamkova, Vaclava; Adamkova, Vanda Gabriela; Kroneislova, Gabriela; Zavora, Jan; Kroneislova, Marie; Huptych, Michal; Lahoda Brodska, Helena (Microorganisms, 2024)
Streptococcus pyogenes, group A streptococci (GAS) bacteriaemia, is a life-threatening infection with high mortality, requiring fast diagnosis together with the use of appropriate antibiotic therapy as soon as possible. Our study analysed data from 93 patients with GAS bacteraemia at the General University Hospital in Prague between January 2006 and March 2024. In the years 2016-2019 there was an increase in GAS bacteraemia. Mortality in the period 2006-2019 was 21.9%; in the period 2020-2024, the mortality increased to 41.4%, p = 0.08. At the same time, in the post-2020 period, the time from hospital admission to death was reduced from 9.5 days to 3 days. A significant predictor of worse outcome in this period was high levels of procalcitonin, >35.1 μg/L (100% sensitivity and 82.35% specificity), and lactate, >5 mmol/L (90.91% sensitivity and 91.67% specificity). Myoglobin was a significant predictor in both compared periods, the AUC was 0.771, p = 0.044, and the AUC was an even 0.889, p ≤ 0.001, respectively. All isolates of S. pyogenes were susceptible to penicillin, and resistance to clindamycin was 20.3% from 2006-2019 and 10.3% in 2020-2024. Appropriate therapy was initiated in 89.1%. and 96.6%, respectively. We hypothesise that the increase in mortality after 2020 might be due to a decrease in the immune status of the population.